Employer provided training in Europe: Determinants and obstacles - Giorgio Brunello; Patricia Wruuck (European Investment Bank (EIB), 2020)
This report looks at employer - provided training in Europe. We start with a brief outline of the economic theory of training. We then look at the recent facts, by combining data from two employer surveys, the European Investment Bank's Investment Survey (EIBIS) and Eurostat's Continuous Vocational Training Survey (CVTS). We review the recent empirical literature on the relationship between economic institutions and training and between training and productivity and consider whether financing constraints hamper the training provision by firms. The paper concludes by discussing policy implications.
Keywords: 330; EU Countries; Economics; Education and training